Estratégias de comando para o controle de carregadores modulares de baterias - Nicolas Tadeu Domingues Fernandes (2021)
The lifetime of Battery Banks has always been a concern in Battery Energy Storage Systems (BESS) and its increasing use in intermittent distributed systems makes this analysis paramount. Work in these areas ranges from studies of failure mechanisms and electrochemical processes to charge strategies. Although the literature extensively covers the development of battery chargers control strategies, a comparison of these strategies remains a literary gap. The inherent conditions ie, State of Health (SoH) and State of Charge (SoC) of each unit in the Battery Energy Storage Systems directly influence the charger control techniques for extending battery lifetime, which makes modular battery chargers an appealing topology for this analysis. This work through a new classification groups charger control strategies presented in the literature into two: Adapted SoC strategies, directly linked to the field of overstress management, and SoH strategies, which are directly linked to the field of wear-out management. The overstress management field aims to keep the units of interest within acceptable operating conditions and its relationship with the increase in the bank’s useful life is only indicated, lacking proof, whether simulation or experimental. The wear out management field aims to keep the units of interest at the same level of degradation and its relationship with the increase in the bank’s useful life is clearly present in the control philosophy. These strategies are compared through the analysis of their dynamics, changing the gain values of the recharge control strategy as well as disturbances in the discharge depth and recharge current, critical factors in storage systems powered by renewable and intermittent sources. The methodology for comparing recharge control strategies includes the study of models. The battery life model allows the characterization of the wear profile of the studied battery. The modular charger model allows the analysis of the operation of control strategies and their implications for the battery recharge and discharge process. The photovoltaic application model allows the calculation of the application’s average DoD, thus allowing to scale the number of bank units. Three distinct cases were simulated using real measurement data from a solar power plant and a battery model provided by MathWorks⃝R , also with real battery data. The results show that the loss of capacity and the throughput of energy strongly depend on the applied strategy. Furthermore, this work analyzes the effect of the estimation process on the action of the recharge controller.